2019
DOI: 10.3928/1081597x-20181113-01
|View full text |Cite
|
Sign up to set email alerts
|

Primary Topography-Guided LASIK: Treating Manifest Refractive Astigmatism Versus Topography-Measured Anterior Corneal Astigmatism

Abstract: PURPOSE: To investigate whether topography-guided laser in situ keratomileusis (LASIK) with anterior corneal astigmatism measured on the WaveLight Contoura (Alcon Laboratories, Inc., Fort Worth, TX) leads to better refractive outcomes compared to treating on the clinically measured manifest refractive astigmatism axis in eyes with primary myopic astigmatism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…Various alternative strategies have been proposed, therefore, to determine the appropriate laser entry for the Treatment sphero-cylindrical refraction. 4,6,9,10,12 The current study was designed to address the question of how to program the WaveLight Contoura ® Vision laser to produce optimal refractive outcomes for eyes in which there is a disparity between Manifest and Topo refractions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various alternative strategies have been proposed, therefore, to determine the appropriate laser entry for the Treatment sphero-cylindrical refraction. 4,6,9,10,12 The current study was designed to address the question of how to program the WaveLight Contoura ® Vision laser to produce optimal refractive outcomes for eyes in which there is a disparity between Manifest and Topo refractions.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the outcomes using the Topo axis were inferior to those obtained with the cylinder axis measured by the manifest refraction. 6 These published findings and the unpublished experiences of others, including the authors of this paper, have led to further discussions about whether the method of programming the laser that was used during the FDA clinical trial produces optimal outcomes.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…3 We recently discussed how poorer outcomes are expected in ACA-treated eyes that ignore ORA, unrelated to a comparison of WFO versus Contoura technology. 4 Much of the study's discussion is a repetition of the research of Motwani, who first described the LYRA protocol. Ozulken et al state: "Motwani showed that HOAs [higher order aberrations] interacting with lower order astigmatism is the main reason for the differences between manifest refraction," 1 but they do not discuss our mathematical three-dimensional quantification that shows that his theory is not valid.…”
Section: Targeting Anterior Corneal Astigmatism With Topography-guidementioning
confidence: 99%
“…Similarly, in a study of 100 eyes of 50 patients, Kanellopoulos 2 reported that topography-guided treatment using topography-modified refraction values yielded better results than the treatment using manifest refraction.In addition, in their study comparing wavefront-optimized (WFO) and topography-guided treatment methods, Kim et al 3 used topography-modified refraction values in the topography-guided treatment group and reported that topography-guided laser in situ keratomileusis induced fewer higher order aberrations (HOAs) and significantly reduced ocular trefoil, corneal total HOAs, and coma. On the contrary, Wallerstein et al 4 have long advocated the use of manifest refraction with topography-guided ablation, and this viewpoint would have us believe that the removal of light scatter via corneal HOA reduction has no effect on the measurable astigmatism whatsoever and that the hand-measured, post-cortical processing-derived astigmatism number is sacrosanct and the correct way to treat.…”
Section: Replymentioning
confidence: 99%